Radiation dose in coronary CT angiography associated with prospective ECG-triggering technique: Comparisons with different CT generations - Sabarudin, A.; Sun, Zhonghua; Ng, K. (Oxford University Press, 2013)
A retrospective analysis was performed in patients undergoing prospective ECG-triggered coronary computed tomography (CT) angiography (CCTA) with the single-source 64-slice CT (SSCT), dual-source 64-slice CT (DSCT), dual-source 128-slice CT and 320-slice CT with the aim of comparing the radiation dose associated with different CT generations. A total of 164 patients undergoing prospective ECG-triggered CCTA with different types of CT scanners were studied with the mean effective doses estimated at 6.8±3.2, 4.2±1.9, 4.1±0.6 and 3.8±1.4 mSv corresponding to the 128-slice DSCT, 64-slice DSCT, 64-slice SSCT and 320-slice CT scanners. In this study a positive relationship was found between the effective dose and the body mass index (BMI). A low radiation dose is achieved in prospective ECG-triggered CCTA, regardless of the CT scanner generation. BMI is identified as the major factor that has a direct impact on the effective dose associated with prospective ECG-triggered CCTA.